ANALISIS DAMPAK LIBERALISASI PERDAGANGAN KAWASAN EKONOMI ASIA TERHADAP KINERJA EKONOMI MAKRO ASEAN - Ichsan Zulkarnaen; Rina Oktaviani; Mangara Tambunan; Yulius Yulius (IPB University, 2012)
This research intends to explore the impact of trade liberalization on macroeconomic performances, especially on Indonesia and other ASEAN Countries. The GTAP model is used as the main tool of analysis. The findings show that the benefit of the trade liberalization is still dominated by developed countries such as Japan and China. The elimination of import tariff results an increase in economic growth and economic welfare on all participated countries. It also results in an increase in GDP deflator and terms of trade which meant decreasing competitiveness. Keywords: Asia trade liberalization, ASEAN countries, GTAP model